A Review on Arsha and its Management with Pathya Apathya in Ayurveda (AYUSHDHARA, 2025)
Arsha, commonly referred to as hemorrhoids, is a prevalent anorectal disorder characterized by swelling and inflammation of the anal vasculature. Nevertheless, many people are still willing to undergo Ayurvedic treatment despite all the modern medicine achievements because of its comprehensive character and focus on prevention. Ayurveda identifies Arsha as one of the Ashta Mahagadas, highlighting its chronicity and potential severity. This review explores the classical Ayurvedic understanding of Arsha, focusing on its etiopathogenesis, classification, and comprehensive management. Particular emphasis is given on the role of Pathya (wholesome dietary and lifestyle practices) and Apathya (unwholesome habits) in both prevention and therapeutic intervention. A thorough literature search was conducted using classical Ayurvedic texts and scientific databases, including PubMed, Google Scholar, and e-Samhita portals. Findings indicate that in the treatment of Arsha, in addition to the medicinal and surgical treatment, such as Bheshaja, Kshara karma, Agnikarma, and Shastra karma, the dietary taboo, as well as discipline and daily routine, should be adhered to. Changes in lifestyle like eating high fibre diets, drinking more water, and adopting the right bowel habits, certain yogic routines are part and parcel of reducing the possibility of recurrent attacks. Conversely, indulgence in spicy food, sedentary habits, suppression of natural urges, and irregular dietary patterns contribute significantly to disease progression. The review highlights that the application of the specific concept of Pathya-Apathya in clinical practice can indeed provide better results in treating patients with Arsha as well as helping them to lead pleasant lives.